Prevalence of anemia cases among pregnant women attending general Hospital and Al-Birket Health Center in the city of Ghat (Journal of Medical Sciences, 2023)
Anemia is one of the most common hematological problems in different parts of the world, especially in developing countries, iron deficiency anemia is the most prevalent nutritional deficiency in the world, pregnant women, young children and adolescents are considered the most vulnerable. Due to the fact that iron deficiency anemia is a serious complication for the health of pregnant women and the fetus ,Therefore, this study was conducted for the purpose of studying the prevalence of anemia among pregnant women in the Ghat region. This study included 95 samples of pregnant women attending Ghat General Hospital and Al-Birket Health Center in Ghat region. Venous blood samples were collected and a complete blood count (CBC) was performed and serum iron was measured, The results of the study showed that the general percentage of anemia prevalence among pregnant women was 27.71%, The cases of the third trimester constituted the highest percentage of anemia at 64%, then the second third at 28%, while the first trimester constituted the lowest prevalence rate of 8% of the total cases of anemia, and , it was found that most of the anemia cases were mild anemia 64 % while 32% of cases moderate anemia and severe anemia at 4%. We conclude from this study that the general incidence of anemia among pregnant women in the Ghat region was moderately severe. Most cases of anemia were suffering from mild anemia.